Potatoes Storage, Price Spread through Various Channels and Marketing Efficiency in Parwan Province, Afghanistan - Lalzai, Faridullah; Jamali, Akhtar Jamal; Naziri, Abdul Mutaleb; Mohammadzai, Gulwali; Mashkoor, Rashidullah; Ebrahimi, Mohammad Shakir (Journal for Research in Applied Sciences and Biotechnology, 2023)
This research paper examined the factors influenced farmers' immediate selling of potatoes after harvest and their storage practices, various factors and limitations affected their selling and storage capacity has been identified and the ground conditions as realistic discussed as well as the price spread and marketing efficiency in the three districts Siyagard, Ghorband, and Shinwari of Parwan province, Afghanistan. The study conducted revealed that farmers primarily sold potatoes to pay for household expenses 57.50 percent and finance agricultural inputs 55.00 percent. Moreover, sold for loan repayment 45.00 percent and limited storage space 52.50 percent play significant roles in immediate selling decisions. The study also showed that farmers stored potatoes for various reasons, such as personal consumption 23.3 percent, anticipating higher prices 24.20 percent, meeting off-season demand 23.3 percent, and exploiting competitive prices 23.3 percent. The study provide insights into the price spread in different market channels, indicating varying profit margins for farmers and intermediaries. Finally, the study highlighted the marketing efficiency under different channels, with Channel III showed the highest efficiency 47 percent in direct distribution, followed by Channel II 32 percent and Channel I 29 percent. These findings highlight the complexities of potato marketing in the Parwan province, Afghanistan which can help policymakers to develop a sustainable approach to inform strategies to improve farmers' income and market efficiency.